"I do it all alone": the burdens and benefits of being diagnosed with, and treated for, colorectal cancer during the Covid-19 pandemic - Dobson, Christina; Deane, Jennifer; Osborne, Beth; Araújo-Soares, Vera; Rees, Colin J.; Angell, Lorraine; Sharp, Linda (Health expectations, 2024)
Introduction The Covid-19 pandemic dramatically altered the way cancer care services were accessed and delivered, including for colorectal cancer (CRC). In the United Kingdom, patients were discouraged from presenting in primary care, many consultations took place remotely, investigative procedures and screening programmes were temporarily suspended, and fewer operations and treatments were delivered. People had to face the practical consequences of having cancer during a pandemic and navigate never before seen pathways, often alone. We examined the experience of being diagnosed and treated for CRC during the pandemic, and the implications of this on people's cancer journeys. Methods Semi-structured interviews were undertaken with people diagnosed with CRC during the Covid-19 pandemic (January 2020-May 2021), in the North East of England. An iterative topic guide was used during interviews, which took place remotely (telephone or Zoom), were audio recorded, pseudo-anonymised and transcribed. Initial transcripts were independently coded by two researchers, and a code ‘bank’ developed for application across transcripts. Development of themes and overarching analytical constructs was undertaken collaboratively by the research team. Results Interviews were conducted with 19 participants, analysed and four key themes identified: (1) The relative threats of Covid-19 and Cancer were not comparable, with cancer seen as posing a far greater risk than Covid-19; (2) Remote consultations were problematic, affecting patients' abilities to build rapport and trust with clinicians, assess nonverbal communication, and feel able to disclose, comprehend and retain information; (3) Stoma follow-up care was seen to be lacking, with long wait times for stoma reversal experienced by some; Finally, (4) Being alone during consultations negatively impacted some peoples' abilities to absorb information, and left them without the support of loved ones at an emotionally vulnerable time. However, some participants preferred being alone at certain points in their pathways, including receiving a diagnosis, and most frequently when receiving in-patient treatment. Conclusion Being alone brought unexpected benefits, absolving people from undertaking emotions work for others, and instead focus on their recovery, however, remote consultations negatively impacted patients' experiences. This study highlights the complex benefits and burdens of pandemic-located cancer journeys, including how these shifted at different points across cancer pathways. Patient or Public Contribution Lorraine Angell, a cancer survivor, has been central to this study from idea conception, contributing to: development of study focus and design; securing funding; production of patient-facing materials; development of interview topic guides; analysis and interpretation of data; and drafting of key findings and manuscripts.
Zuerst veröffentlicht: 14. Juni 2024
Gesehen am 21.11.2024